2019
DOI: 10.1097/cin.0000000000000552
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Web-Based Preoperative and Postoperative Patient Care Education on Nursing Students

Abstract: This study examined the effect of Web-based preoperative and postoperative patient care education among undergraduate nursing students. This was an experimental, randomized controlled study. The study included 305 nursing students (experimental group: n = 155, control group: n = 150), who were assessed with the following instruments: the Preoperative and Postoperative Care Knowledge Test, Preoperative and Postoperative Care Skill Control List, Clinical Decision Making in Nursing Scale, and Nursing Student Clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Moreover, the clinical practice of students in surgical units could increase their level of knowledge. Durmaz Edeer et al 3 reported that clinical practice can improve learning abilities. However, comparing the preoperative care competence of nursing and midwifery students is difficult because of relatively limited studies in this area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the clinical practice of students in surgical units could increase their level of knowledge. Durmaz Edeer et al 3 reported that clinical practice can improve learning abilities. However, comparing the preoperative care competence of nursing and midwifery students is difficult because of relatively limited studies in this area.…”
Section: Discussionmentioning
confidence: 99%
“… 2 Preoperative care aims to identify risk factors that could lead to complications for patients after surgery. 3 Patients should be prepared physically, physiologically, and emotionally, and spiritually for surgery to have a positive post‑operative recovery. 4 It was found that preoperative patients with high religiosity levels had lower levels of anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…With the medium methodological quality, preoperative education was found to be helpful in improving the prognosis of patients undergoing cardiac surgery [ 28 ] because it may enhance patients’ knowledge; besides, meeting their information needs could also mitigate their distress [ 54 ]. However, our umbrella-shaped review shows that information intervention cannot effectively reduce patients’ transfer anxiety, which may be related to our use of quantitative rather than qualitative methods to investigate transfer anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Researches showed that the uncertainty accounted for 30.2% of the factors that cause family members' transfer anxiety, and providing information was a key factor in reducing uncertainty and anxiety [38,39]. Preoperative education was also helpful to improve the prognosis of patients undergoing cardiac surgery [31] because it may enhance patients' knowledge; besides, meeting their information needs could also mitigate their distress [40]. However, our umbrella-shaped review shows that information intervention cannot effectively reduce patients' transfer anxiety, which may be related to our use of quantitative rather than qualitative methods to investigate transfer anxiety.…”
Section: Summary Of Main Ndingsmentioning
confidence: 99%